Russian-Vietnamese Cooperation in Energy Sector - Thi Lan Nguyen; Elena Fedorovna Chernenko (Vestnik RUDN. International Relations, 2018)
The abundance of energy resources including renewables and non-renewables is central to the development of energy sector. However, other decicive factors like technology and human resources turn naturally-bestowed gifts into economic gains for properity. In the circumstance of being an invaded country in the 1950s, the young Democratic Republic of Vietnam prioritized formation of energy sector in the economic development plan to be more self-reliant in energy security for a harsh war against much more powerful enermies. A single international source of supports for the very young country at that time was communist allies. The Soviet Union assumed a major responsibility as the largest benefactor for the Democratic Republic of Vietnam in the war-time. In addition to millitary and logistic aids for the Democratic Republic of Vietnam in North Vietnam to struggle with the US-backed Government of the Republic of Vietnam in South Vietnam for unification, the Soviet Union also actively supported it to implement the 5-year economic plans for socialism development including formation and development of the energy sector. In the post-war time, they continued to support the newly-unified country, the Socialist Republic of Vietnam, to develop the energy sector as its spreadhead economic sector. The Russian Federation and Vietnam continue to deepen the bilateral cooperation in energy sector with the successful management of multibillion dollar joint-ventures in the oil and gas industry and implement many projects in the energy sector as a whole after the collapse of the Soviet Union. In assessment of the achivements of Russia- Vietnam cooperation, the bilateral parternship in energy sector emerges as the most prominent area of cooperation over the 68-year old history of cooperation. This article is aimed to provide a brief history of bilateral cooperation in the energy sector with an emphasis on the central role of the Soviet Union and later Russian Federation in forming and developing the energy sector of Vietnam. Prospects of cooperation are also a matter of analysis in this article.